Analisis Pengaruh Vaksin Covid-19 Terhadap Nilai HbA1c Pasien DM Tipe-2 Di Puskesmas: Studi Retrospektive - Setyaningsih, Intan Wiji; Kurniasih, Khamdiyah Indah; Setianingsih, Siti (Journal of Pharmaceutical and Health Research, 2024)
Coronavirus Disease 2019 (Covid-19) is a dangerous type of infection that causes death and is at risk in DM patients, so the selection of vaccines is very selective, especially moderna or pfizer vaccines that will know the increase in blood glucose. The purpose of this study was to determine the description and relationship of HbA1c values in type 2 DM patients after the 2nd dose of moderna or pfizer Covid-19 vaccine at Mrebet Health Center. The method used was analytical research with a retrospective observational approach conducted by conducting interviews with DM patients in the form of compliance with drug use, remaining drug use in 1 month, and sugar diet. Measurement of HbA1c values obtained from 3 months before and 3 months after the 2nd dose of moderna or pfizer vaccine. The results of the study obtained 32 DM prolanis patients, where the most patients were aged 45 - 65 years as many as 28 (87.5%), and female gender 27 (84.4%). The type of vaccine obtained was 25 (78.1%) moderna vaccine and 7 (21.9%) pfizer vaccine. The average pre-vaccine and post-vaccine HbA1c values increased by 0.3% from 8.0% to 8.3% and a standard deviation of 0.10. Based on the analysis, the p-value of 0.000 <0.050 was obtained, so statistically there was a slight increase with almost the same value between HbA1c values in type 2 DM patients after the Covid-19 moderna vaccine or the 2nd dose of pfizer. Conclusion There is an increase between pre-vaccine and post-vaccine HbA1c values and there is a relationship between HbA1c values in patients with type 2 DM after the Covid-19 moderna or pfizer 2nd dose vaccine.